Clearing and Masking Agents in Pretargeting Strategies - Markus Staudt; Matthias M. Herth (MDPI AG, 2023)
'Pretargeting' led to increased target-to-background ratios of nanomedicines in short timeframes. However, clearing or masking agents are needed to reach the full potential of pretargeted approaches. This review gives an overview of clearing and masking agents employed in pretargeting strategies in both preclinical and clinical settings and discusses how these agents work.